STUDI KELAYAKAN USAHATANI CABAI BESAR (Capsicum Annum L.) DI KELURAHAN LEMPAKE KECAMATAN SAMARINDA UTARA KOTA SAMARINDA - Dely Yanti (Agrifor : Jurnal Ilmu Pertanian dan Kehutanan, 2014)
Feasibility Study of Curly Chilli Farming (Capsicum annum L.) in the urban village of Lempake, North Samarinda sub district, Samarinda Municipality.  The purpose of this study were: (1) To determine the revenue and profit economically curly chili farming and (2) to determine the withdrawal or efensiensi curly chili farm in the Village District Lempake North Samarinda.The study was conducted from September to October 2012 in the Village district Lempake North Samarinda.Sampling for the study were calculated using proportional Stratiefied Random Sampling, respondents selected the peasant farming chili seeking kinky as 10 farmers. Data collected consists of: primary data and secondary data. The data include: total cost, Revenue, Revenue, break even point and efensiensi their farm.The result showed that: (1) income curly chili farming in one growing season is Rp73.902,149,- with an average of Rp 7.390,215,/ha, (2) the cost of production significantly affect the income generated by farming chilli curls and (3) R/C ratio 2,39 average which means that for every expenditure of Rp 15,000- you will get a revenue of  Rp 38,350,-